DINAMIKA DAN PERAN KEPEMIMPINAN DALAM PENGEMBANGAN ORGANISASI - Ni Made Gunastri (STIMI Handayani Denpasar, 2012)
In this millennium century there is no place without competition and competition has been and will become new principles,because the business worldwhich is open and compete to carry out better thing. These conditions require achange and development continuesly. All of these if not immediately improvewill threaten the survival of the organization / company life. In other words theimpact of globalization will be a big and serious threat if organization doesn’thave strong, reliable and dynamic leadership as according with development oforganization environment strategic (internal and external).In the process of organizational development very needed leadershiprole undertaken by a leader and leadership effectiveness can be judged by how he able to overcome the main problems and challenges faced. The key to create andcontinuing organization in the 21st century in order to success is leadership, donot only at the top of the hierarchy, but in the entire of organization. This means that inthe coming decades we will see the emergence of new organizational forms whichovercome with more rapid movement and more competitive environment and newtypes of workers, at least in a successful company.Suitable leadership can be applied at this time in developingof organization is superleadership that is someone who leads theirself asan empowering leader . A Superleadership will make empower, train, teach,reward and arranging the environment to make his subordinates able tolead themselves and can show its performance.